Proces o czary w podkrakowskiej wsi Krowodrza w 1698 roku - Uruszczak, Wacław (Studia Iuridica Toruniensia, 2012)
<!–[if gte mso 9]> <![endif]–> The article consist of the two parts. In the fi rst one, the Author devotes a few general sentences to the witchcraft, the trails for the witchcraft, the role of the Roman Catholic Church in its reduction – in the end – to abolition of the witchcraft as a criminal off ence. In the second part the Author describes the trail, which took place in the near Cracow village Krowodrza in 1698. In the front of the local court, Regina Budzynka accused Stanisław Dudek of the witchraft slander. The court found the accusation of witchcraft as false. Defendant had to cancel his slander and he was sentenced for 3 days in a jail and fi ned. <!–[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>